Botulinum toxin type A for genitofemoral neuralgia: A case report - Tereshko, Yan; Enrico, Belgrado; Christian, Lettieri; Dal Bello, Simone; Merlino, Giovanni; Gigli, Gian Luigi; Valente, Mariarosaria (Frontiers in Neurology, 2023)
Genitofemoral neuralgia is an uncommon pain disorder that could be resistant to conventional treatment. A 78-year-old woman with refractory right genitofemoral neuralgia was treated with BoNT/A subcutaneous injections; the treatment was performed three times with significant pain improvement, although temporary, and without adverse events. BoNT/A may be a promising alternative intervention in the setting of genitofemoral neuralgia refractory to oral and/or topical treatment.